2017
DOI: 10.4172/2329-8863.1000279
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Crop Rotation Including Cereals and Green Manures on Potato Yield and Nitrogen Nutrition and Soil Properties

Abstract: Soil quality decline is a common concern in potato production systems. Including cereals and green manures (GMs) in potato rotation could improve soil productivity and sustain potato (Solanum tuberosum L.) yields and quality. This experiment initiated in Québec, eastern Canada, assessed the effects of two cycles of 2-yr potato rotations with cereals and GMs on soil properties and potato yield and quality, and on disease incidence -1 ) were applied to potato. After two rotation cycles in 2011, soils under cerea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…The DS system also resulted in overall significant increases in total and marketable yield relative to SC, SQ, and PP under non-irrigated conditions. These increases were presumably due to the beneficial effects of the added green manure and cover crops in reducing potential pathogens and soilborne diseases, and maintaining various soil health parameters, as has been observed in other potato systems [12,43,44]. As previously reported, DS resulted in lower incidence and severity of multiple soilborne diseases (including stem canker, black scurf, and common scab), as well as significant effects on soil microbial community characteristics, but more modest effects on soil chemical and biological parameters [20,21].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The DS system also resulted in overall significant increases in total and marketable yield relative to SC, SQ, and PP under non-irrigated conditions. These increases were presumably due to the beneficial effects of the added green manure and cover crops in reducing potential pathogens and soilborne diseases, and maintaining various soil health parameters, as has been observed in other potato systems [12,43,44]. As previously reported, DS resulted in lower incidence and severity of multiple soilborne diseases (including stem canker, black scurf, and common scab), as well as significant effects on soil microbial community characteristics, but more modest effects on soil chemical and biological parameters [20,21].…”
Section: Discussionmentioning
confidence: 76%
“…Although only one potato variety, Russet Burbank, which is the predominant processing variety grown commercially in the northeast, was used in this study, observed results should be generally applicable to other potato varieties as well. Previous studies in this region have indicated similar responses to rotations, amendments, and fertilization in multiple different potato varieties [29][30][31][32]36], and improvements in soil health have been associated with increases in yield across not only different potato varieties but many different crops as well [4,6,[12][13][14][15]44].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Se ha demostrado que especies de la familia Brassicaceae poseen componentes naturales como los glucosinolatos, producidos a partir del metabolismo secundario de las plantas que al ser utilizadas como abonos verdes liberan una serie de compuestos tóxicos, en especial la capacidad biofumigante de los isotiocianatos, que limitan directamente el desarrollo hongos patógenos del suelo (Larkin y Griffin, 2007;Vandicke et al, 2020). Dayegamiye et al, (2017), exponen que la incorporación al suelo de cereales como variedades de rápido crecimiento de cebada, avena o trigo, cuyo aporte considerable de biomasa trae consigo efectos positivos sobre las propiedades del suelo y su microbiota; condiciones que predisponen una menor incidencia de fitopatógenos.…”
Section: Introductionunclassified
“…Another potential source of organic fertilizer in the present study area is using green manure such as clover and lupine undersowing with cereals or grown in pure stands in the rotation system. The important soil quality parameters such as the organic matter of the soil, soil nutrients, soil aeration and water holding capacity would be improved that in turn make the crop production more sustainable (Ndayegamiye et al 2017).…”
Section: Introductionmentioning
confidence: 99%